Time-of-Flight Measurement of a 355-nm Nd:YAG Laser-Produced Aluminum Plasma - Baclayon, M. F.; Alonzo, C. A.; Garcia, W. O. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 15 No 1 (2003), 2007)
An aluminum target in air was irradiated by a 355-nm Nd:YAG laser with a pulse width of 10 ns and a repetition rate of 10 Hz. The emission spectra of the laser-produced aluminum plasma were investigated with varying distances from the target surface. The results show the presence of a strong continuum very close to the target surface, but as the plasma evolve in space, the continuum gradually disappears and the emitted spectra are dominated by stronger line emissions. The observed plasma species are the neutral and singly ionized aluminum and their speeds were investigated using an optical time-of-flight measurement technique. Results show that the speeds of the plasma species decreases gradually with distance from the target surface. Comparison of the computed speeds of the plasma species shows that the singly ionized species have relatively greater kinetic energy than the neutral species.